Indonesian Diaspora Halal Cuisine as Cultural Diplomacy - Moh Rizal Riandi; Mahbubi; Ayu Safitri; St Susi Astika Sari; Koyyimahtul Munawaroh (Mahkota Science Publishers, 2025)
This study aims to construct a conceptual model of how halal cuisine, as practised by members of the diaspora, functions as a mechanism that transforms religious norms and process standards into symbolic capital and cross-cultural trust by mapping the halal gastrodiplomacy value chain from upstream to downstream, linking regulations. This study utilises library research to conduct an in-depth analysis of various scientific sources, constructing a comprehensive and reflective theoretical framework on Indonesian diaspora halal cuisine as a form of cultural diplomacy. The results conclude that Indonesian diaspora halal cuisine is the most concrete and political form of cultural diplomacy, as it blends taste, values, and strategy into a new global language about Indonesia. It demonstrates how the diaspora kitchen has evolved into a space for negotiation between faith and the market, between authenticity and adaptation, and between spirituality and commodification. Halal cuisine is no longer merely a religious symbol, but has evolved into an instrument of soft power that connects identity politics, the creative economy, and national image. From the tension between values and exchange rates, the most honest diplomacy of taste is born, one that does not subjugate but invites the world to understand Indonesia through the aroma of halal, warmth, and humanity.